ANALYSIS OF PROFIT FUNCTION AND RETURNS TO SCALE OF RICE FARMING IN TIDAL AND FRESHWATER SWAMPLANDS IN SOUTH KALIMANTAN - Rifiana Rifiana; Kamiliah Wilda; Yudi Ferrianta (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2017)
The purpose of this study was to estimate the production and profit function by farmers and to analyze the relative economic efficiency of rice farming in two typologies of wetland, tidal swampland and freshwater swampland. The analysis showed that the production facilities in the study area were very influential on the rice farming profit, so an increase in the high price of production facility would lead to a decrease in profit, which in turn would lower the level of farmers’ welfare. Under optimal conditions where maximum profit was reached, the effects of variable input prices and the input number remained significant except for the value of the equipment used. Based on the value of the coefficient function of fertilizer demand, pesticide and labor were inelastic towards the price while the seed input was elastic. Rice farming in the study area had decreasing returns to scale. It indicated that the increase in inputs was higher than the increase in returns.